Single dose, CYP2D6 genotype‐stratified pharmacokinetic study of atomoxetine in children with ADHD. Issue 6 (12th January 2016) - Brown, JT; Abdel‐Rahman, SM; van Haandel, L; Gaedigk, A; Lin, YS; Leeder, JS
Abstract : The effect of CYP2D6 genotype on the dose‐exposure relationship for atomoxetine has not been well characterized in children. Children 6–17 years of age diagnosed with attention‐deficit hyperactivity disorder (ADHD) were stratified by CYP2D6 genotype into groups with 0 (poor metabolizers [PMs], n = 4), 0.5 (intermediate metabolizers [IMs], n = 3), one (extensive metabolizer [EM]1, n = 8) or two (EM2, n = 8) functional alleles and administered a single 0.5 mg/kg oral dose of atomoxetine (ATX). Plasma and urine samples were collected for 24 (IM, EM1, and EM2) or 72 hours (PMs). Dose‐corrected ATX systemic exposure (area under the curve [AUC]0‐∞ ) varied 29.6‐fold across the study cohort, ranging from 4.4 ± 2.7 μM*h in EM2s to 5.8 ± 1.7 μM*h, 16.3 ± 2.9 μM*h, and 50.2 ± 7.3 μM*h in EM1s, IMs, and PMs, respectively ( P < 0.0001). Simulated steady state profiles at the maximum US Food and Drug Administration (FDA)‐recommended dose suggest that most patients are unlikely to attain adequate ATX exposures. These data support the need for individualized dosing strategies for more effective use of the medication.